Chronic disseminated cryptococcosis without meningeal involvement in a severely immunosuppressed HIV-infected patient successfully treated with fluconazole - Tatiane da Silveira Yonekura; Soraya Devi Macedo; Fernanda Gonçalves Moya; José Ernesto Vidal (Medical Mycology Case Reports, 2022)
A 43-year-old female with advanced HIV infection presented with two chronic skin lesions. Cutaneous cryptococcosis was confirmed and pulmonary cryptococcosis was suspected. The patient was neurologically asymptomatic and the cerebrospinal fluid cryptococcal antigen lateral flow assay was negative. She received oral fluconazole and had resolution of the skin lesions and significant improvement of the lung lesions. We report a person with AIDS with chronic disseminated cryptococcosis without meningeal involvement successfully treated with oral fluconazole.